2018
DOI: 10.1002/joc.5457
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnection influence of precipitation‐bearing synoptic types over the Snowy Mountains region of south‐east Australia

Abstract: Understanding the causes of precipitation and variability of precipitation in areas such as the Snowy Mountains is critical for regional water resource management. A number of climate drivers influence precipitation in this region. This research demonstrates that relationships are not stationary over time, and represents a step forward in understanding the complex interactions between teleconnections and synoptic atmospheric circulation that drive precipitation variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Australia is characterized by an extremely complex hydroclimate, with severe droughts, interspersed with flooding rains, presenting significant challenges for water resource supply and management (Theobald et al ., 2018). Australian Northwest Cloudbands (NWCBs) are synoptic‐scale baroclinic systems which transport moisture from the tropical northeast Indian Ocean to southeast Australia (Reid et al ., 2019; Chen et al ., 2020; Wu et al ., 2020; Ye et al ., 2020; McGowan et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Australia is characterized by an extremely complex hydroclimate, with severe droughts, interspersed with flooding rains, presenting significant challenges for water resource supply and management (Theobald et al ., 2018). Australian Northwest Cloudbands (NWCBs) are synoptic‐scale baroclinic systems which transport moisture from the tropical northeast Indian Ocean to southeast Australia (Reid et al ., 2019; Chen et al ., 2020; Wu et al ., 2020; Ye et al ., 2020; McGowan et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies comparing SOMs with other classi cation methods (Fleig et al 2010;Huth 2010;Tveito 2010;Lykoudis et al 2010;Broderick and Fealy 2015;Trigo et al 2016;Palm et al 2017) clearly showed that different methods turn out to be optimum depending on the application, it has been the SOM that sparked a new interest in synoptic climatology owing to its novel point of view on circulation variability (Sheridan and Lee 2011). This interest resulted in a wide range of studies on circulation in outputs of reanalyses and climate models, links between circulation and various atmospheric and environmental phenomena, as well as links between synoptic-scale CTs to large-scale teleconnections, bringing new insights into circulation over Asia (Liu et al 2016;Gao et al 2019;Ohba and Sugimoto 2019), Polar regions (e.g., Schuenemann et al 2009;Bezeau et al 2015;Yu et al 2018), Australia and New Zealand (e.g., Jiang et al 2013;Huva et al 2015;Gibson et al 2016a,b;Harrington et al 2016;Theobald et al 2016Theobald et al ,2018, Europe (e.g., Tymvios et al 2010;Polo et al 2011), North America (e.g., Newton et al 2014;Cassano et al 2016Cassano et al ,2017Swales et al 2016;Sugg and Konrad II 2017;Díaz-Esteban and Raga 2018), South America (Espinoza et al 2012;Rodríguez-Morata et al 2018), and southern Africa (e.g., Lennard and Hegerl 2015;Engelbrecht and Landman 2016;Wolski et al 2018;Quagraine et al 2019).…”
Section: Introductionmentioning
confidence: 99%